2001
DOI: 10.1590/s1516-35982001000300027
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição da enzima fitase sobre o desempenho e a digestibilidade ileal de nutrientes

Abstract: RESUMO -Conduziu-se um experimento utilizando 384 pintos de corte machos, Avian Farm, para se avaliar o efeito da fitase sobre o desempenho das aves e os coeficientes de digestibilidade ileal aparente da matéria seca (MS), da proteína bruta (PB), da energia bruta (EB), do fósforo (P) e do cálcio (Ca) e os valores de energia digestível ileal aparente (EDIap) e energia metabolizável aparente corrigida pelo balanço de nitrogênio (EMAn) de dietas à base de milho e farelo de soja com diferentes níveis de Ca e P dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
23

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 14 publications
2
9
1
23
Order By: Relevance
“…The results obtained for the total rearing period showing that increasing phytase levels had negative effects on performance parameters are different from literature results (Tejedor et al, 2001;Lan et al, 2002;Wu et al, 2004). However, in literature, phytase nutritional matrix results were not considered in the formulation of the experimental diets, and therefore Using low available phosphorus levels and phytase inclusion, Persia & Saylor (2006) showed that phytase improved the performance of 8-to 22-day-old broilers, as opposed to Angel et al (2006), who did not find any broiler performance differences during the starter phase when adding phytase to low available phosphorus diets.…”
Section: Resultscontrasting
confidence: 99%
“…The results obtained for the total rearing period showing that increasing phytase levels had negative effects on performance parameters are different from literature results (Tejedor et al, 2001;Lan et al, 2002;Wu et al, 2004). However, in literature, phytase nutritional matrix results were not considered in the formulation of the experimental diets, and therefore Using low available phosphorus levels and phytase inclusion, Persia & Saylor (2006) showed that phytase improved the performance of 8-to 22-day-old broilers, as opposed to Angel et al (2006), who did not find any broiler performance differences during the starter phase when adding phytase to low available phosphorus diets.…”
Section: Resultscontrasting
confidence: 99%
“…The metabolizable energy and apparent metabolizable energy corrected for nitrogen from 15-20 days of age did not differ among the treatments (Table 5), so the enzyme phytase was not able to provide energy increase as enunciated by Tejedor et al (2001), who worked with different breed of broiler chickens (Avian Farm) from the one used in this study. Lan et al (2002), when analyzing the metabolizable energy content in the corn and soybean based feed supplemented with phytase enzyme (250-1000 uft kg -1 ) for Avian chickens in the initial and final phases, found higher values of apparent metabolizable energy when compared to a diet with normal levels of phosphorus and without enzyme supplementation.…”
Section: Resultsmentioning
confidence: 87%
“…Boling et al (2000) reported that supplementation of diets with phytase did not improve ileal digestibility of amino acids in chicks. In contrast, Tejedor et al (2001) evaluated 10-24 day old chickens, and found better digestibility values of calcium, phosphorus, protein and apparent energy with the addition of phytase (500-750 uft kg -1 (unit of phytase per kg)) and a better utilization of protein, for example, by breaking the nutrient complex (proteinphytic acid) by the use of phytase breaking and releasing phytate protein and amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para a variável ganho de peso, os dados foram iguais, o que pode ser explicado pela digestibilidade ileal da proteína bruta, do cálcio e do fósforo, que, quando usada fitase, aumenta a quantidade de nutrientes [23], o que justificaria também o peso final das aves.…”
Section: Resultsunclassified